Associations of Antiphospholipid Antibodies With Splanchnic Vein Thrombosis. Issue 4 (January 2015) - Qi, Xingshun; De Stefano, Valerio; Su, Chunping; Bai, Ming; Guo, Xiaozhong; Fan, Daiming; Gao., Chun
<x xml:space="preserve">Abstract</x> Abstract Splanchnic vein thrombosis (SVT) refers to Budd–Chiari syndrome (BCS) and portal vein system thrombosis (PVST). Current practice guidelines have recommended the routine screening for antiphospholipid antibodies (APAs) in patients with SVT. A systematic review and meta-analysis of observational studies was performed to explore the association between APAs and SVT. The PubMed, EMBASE, and ScienceDirect databases were searched for all relevant papers, in which the prevalence of positive APAs or levels of APAs should be compared between BCS or noncirrhotic PVST patients versus healthy controls, or between cirrhotic patients with portal vein thrombosis (PVT) versus those without PVT. Fourteen studies were eligible. Only 1 study evaluated the role of APAs in BCS patients and found that positive immunoglobulin (Ig) G anticardiolipin antibody (aCL) was more frequently observed in BCS patients than in healthy controls; however, the associations of other APAs with BCS were not evaluated. Positive IgG aCL was more frequently observed in noncirrhotic patients with PVST than in healthy controls; however, other APAs, such as IgM aCL, lupus anticoagulants (LAs), anti-β2-glycoprotein-I antibody (aβ2GPI), and aβ2GPI-oxidized low-density lipoprotein antibody (ox-LDL) were not associated with noncirrhotic PVST. Positive unclassified aCL was more frequently observed in cirrhotic patients with PVT than in those without PVT; however, the association of IgG aCL and IgM aCL with the development of PVT in liver cirrhosis remained inconsistent among studies. The risk of BCS and noncirrhotic PVST might be increased by positive IgG aCL but not IgM aCL, LA, aβ2GPI, or aβ2GPI ox-LDL. However, the evidence regarding APAs in BCS originated from only 1 study. The association between APAs and PVT in liver cirrhosis was unclear.